The optimization of electrochemical immunosensors to detect epithelial sodium channel as a biomarker of hypertension - Tias Febriana Hanifa Lestari; Riyanto Setiyono; Nina Tristina; Yulia Sofiatin; Yeni Wahyuni Hartati (International Association of Physical Chemists (IAPC), 2023)
The epithelial sodium channel (ENaC) is a transmembrane protein that regulates the balance of sodium salt levels in the body through its expression in various tissues. The increase in sodium salt in the body is related to the expression of ENaC, thereby increasing blood pressure. Therefore, overexpression of the ENaC protein can be used as a biomarker for hypertension. The detection of ENaC protein using anti-ENaC in the biosensor system has been optimized with the Box-Behnken experimental design. The steps carried out in this research are screen-printed carbon electrode modification with gold nanoparticles, then anti-ENaC was immobilized using cysteamine and glutaraldehyde. Optimum conditions of the experiment, such as anti-ENaC concentration, glutaraldehyde incubation time, and anti-ENaC incubation time, were optimized using the Box-Behnken experimental design to determine the factors that influence the increase in immunosensor current response and the optimum conditions obtained were then applied to variations in ENaC protein concentrations. The optimum experimental conditions for anti-ENaC concentration were 2.5 µg/mL, the glutaraldehyde incubation time was 30 minutes, and the anti-ENaC incubation time was 90 minutes. The developed electrochemical immunosensor has a detection limit of 0.0372 ng/mL and a quantification limit of 0.124 ng/mL for the ENaC protein concentration range of 0.09375 to 1.0 ng/mL. Thus, the immunosensor generated from this study can be used to measure the concentration of normal urine samples and those of patients with hypertension.